Improvement in dye sensitized solar cell efficiency through functionalization of redox mediators and passivation of the photoanode using a home-built atomic layer deposition system - Thomas, Joshua D., author; Prieto, Amy L., advisor; Fisher, Ellen R., committee member; Menoni, Carmen S., committee member; Sampath, Walajabad S., committee member (Colorado State University. Libraries, 2017)
The efficiency of dye sensitized solar cells (DSSCs) is driven based on the contributions of a vast array of kinetic and thermodynamic processes which must all function in sync with one another. The redox mediator factors into a majority of these processes and thus its proper function is vital to adequate function of the DSSC as a whole. The function of the redox mediator can be altered in two ways: changing the identity of the redox couple used and modifying one of the components which the redox couple is interacting with. Herein, both methods have been performed to optimize the properties and processes involved in efficient DSSC function. Several cobalt bipyridine coordination complex type mediators have been synthesized and differentiated through the modification of the ligand structure. The purpose of the modification was to generate complexes with more positive redox potentials to increase the open circuit voltage of the cells. Subsequently, attempts were made to further modify the ethyl ester substituted ligands which yielded the highest redox potential in order to provide higher stability for the resulting mediator. While the outcome of the synthesis was unsuccessful at this point, promising results have been shown. Further, an apparatus was constructed in order to cheaply perform atomic layer deposition of aluminum oxide on the surface of the mesoporous titanium dioxide photoanodes for DSSCs. Atomic layer deposition has been shown to reduce the rate of recombination with the oxidized mediator. In this case, improvement in the open circuit voltage of the cell was shown. However, the overall improved performance of the DSSCs shown in the literature could not be replicated. It is hoped that more high resolution analytical techniques could be used to elucidate the deficiencies still present in the use of this technique.
Keywords: bipyridine; atomic layer deposition; dye sensitized solar cells